The Quality Management System of One Polytechnic College - Jose Ariel Ibarrientos (Camarines Sur Polytechnic Colleges, 2022)
The purpose of this research is to evaluate the Quality Management System (QMS) of Camarines Sur Polytechnic Colleges (CSPC) as an ISO 9001-2015 certified state college and identify the benefits derived by the college along with its certification. Process owners, teaching and non-teaching personnel, and students' perceptions were validated using weighted mean and rank order statistical designs. The study revealed that they were satisfied with the customer focus, leadership, engagement of people, process approach, continual improvement, evidence-based decision-making, and systematic approach to management. As a result of the ISO certification of the college, it gained a positive image to the community and raised to competitors' level or even at a higher level, increased the quality of services, and raised staff awareness were among the positive remarks of the college stakeholders. As an ISO-certified institution, the college was able to identify difficulties early on, allowing for swift solutions to avoid repeating mistakes and achieving local, national, and international quality recognition. As an ISO-certified institution, the college was able to identify difficulties early on, allowing for swift solutions to avoid repeating mistakes and achieving local, national, and international quality recognition. There is no significant difference in perceived satisfaction among the three groups of respondents, according to Freidman's test. Although the analysis reveals a high level of satisfaction, a proposed suggestion will make the college's QMS more vibrant and value-adding.